Case Report: Glomerular microangiopathy and reversible renal toxicity during prolonged bevacizumab therapy in ovarian cancer - Kwon, Jungheon; Choe, Misun; Paek, Jin Hyuk; Park, Woo Yeong; Jin, Kyubok; Han, Seungyeup; Cho, Chi-Heum; Kim, Yaerim (Frontiers in Oncology, 2026)
BackgroundBevacizumab, a VEGF-A inhibitor widely used in ovarian cancer, is associated with kidney adverse effects ranging from mild proteinuria to thrombotic microangiopathy (TMA). However, the longitudinal course, reversibility, and spectrum of kidney-limited injury remain under-characterized.Case reportWe describe three patients with ovarian cancer who developed proteinuria during prolonged bevacizumab therapy, including one with biopsy-proven kidney-limited glomerular microangiopathy. Proteinuria emerged after 6 to 12 months of exposure in all cases. Kidney function remained preserved throughout treatment. All three patients discontinued bevacizumab, after which proteinuria consistently improved. Two patients experienced complete resolution within 3 to 6 months, and one showed marked reduction to dipstick 1 plus by three months. Kidney biopsy in one case revealed double-contour basement membrane changes and subendothelial electron-dense deposits, confirming kidney-limited TMA without systemic microangiopathic findings.ConclusionThese cases illustrate the characteristic time course of bevacizumab-induced kidney toxicity, highlight the reversibility of proteinuria following drug discontinuation, and demonstrate that bevacizumab can induce kidney-limited TMA in the absence of systemic microangiopathic features. Multidisciplinary management is essential to balance oncologic benefit with kidney safety.